Mapping chromatic pathways in the Drosophila visual system. - Lin, T.Y.; Luo, J.; Shinomiya, K.; Ting, C.Y.; Lu, Z.; Meinertzhagen, I.A.; Lee, C.H. (Journal of Comparative Neurology, 2016)
In Drosophila, color vision and wavelength-selective behaviors are mediated by the compound eye's narrow-spectrum photoreceptors R7 and R8 and their downstream medulla projection (Tm) neurons Tm5a, Tm5b, Tm5c, and Tm20 in the second optic neuropil or medulla. These chromatic Tm neurons project axons to a deeper optic neuropil, the lobula, which in insects has been implicated in processing and relaying color information to the central brain. The synaptic targets of the chromatic Tm neurons in the lobula are not known, however. Using a modified GFP reconstitution across synaptic partners (GRASP) method to probe connections between the chromatic Tm neurons and 28 known and novel types of lobula neurons, we identify anatomically the visual projection neurons LT11 and LC14 and the lobula intrinsic neurons Li3 and Li4 as synaptic targets of the chromatic Tm neurons. Single-cell GRASP analyses reveal that Li4 receives synaptic contacts from over 90% of all four types of chromatic Tm neurons, whereas LT11 is postsynaptic to the chromatic Tm neurons, with only modest selectivity and at a lower frequency and density. To visualize synaptic contacts at the ultrastructural level, we develop and apply a "two-tag" double-labeling method to label LT11's dendrites and the mitochondria in Tm5c's presynaptic terminals. Serial electron microscopic reconstruction confirms that LT11 receives direct contacts from Tm5c. This method would be generally applicable to map the connections of large complex neurons in Drosophila and other animals. J. Comp. Neurol. 524:213-227, 2016. © 2015 Wiley Periodicals, Inc.